IMPLEMENTASI DALAM PENYELESAIAN PERMASALAHAN AHLI WARIS PENGGANTI (STUDI BANDING BERDASARKAN HUKUM WARIS ISLAM DAN HUKUM WARIS PERDATA) - Sarijo Sarijo; Akhmad Khisni (Jurnal Akta, 2017)
The study aims to determine the extent to which the replacement of substituted heirs in the case of a substituted heirs system, the implementation of substituted heirs and parts thereof, and the similarities and differences of substitute heirs under the Law of Inheritance and the Law of Inheritance of the Civil Code.The research used with approach method that is juridical normative method is legal research done by giving priority to researching library materials and documents. The specification in this research is using analytical descriptive, this method aims to provide an overview that is done by using a qualitative way that consists of: Theory-theory of law, legal doctrines, as well as opinions from legal experts.The results of this study and discussion: 1) The system of heirs according to Islamic Law is "the amount of property of the deceased in the net, after deducting the payment of the debts of the testator". Whereas in the law of the inheritance of the Civil Code there is no known regulatory difference on the basis of the kind or origin of goods left by the heirs.2) According to the Islamic inheritance law that the lineage entitled to obtain part of the substitute is replaced by a downward straight line, from a straight line upward and from a straight line to the side. Meanwhile, according to the law of the Civil Code inheritance from Hazairin's teaching that the brother of his father, both male and female, is not a barrier to replace his father's position, it is most important that his father had died earlier than the heir (grandfather). 3) The equality of the surrogate heirs in both laws is a person who succeeds the heirs who first passed away from the heirs who should have acquired the inheritance, and the replaced heir is the link between a person who succeeds and heirs. While the difference in terms of replacing the position of his father and: the rights obtained by the successor heirsKeywords: heirs, surrogate heirs, Mawali, Islamic Inheritance Law, Inheritance Law of the Civil Code.